Evaluation of electroacupuncture as a non-pharmacological therapy for astrocytic structural aberrations and behavioral deficits in a post-ischemic depression model in mice - Wang, Jingwen; Deng, Xin; Jiang, Jin; Yao, Zhengyu; Ju, Yaxin; Luo, Yong (Frontiers in Behavioral Neuroscience, 2023)
Background: Ascending clinical evidence supports that electroacupuncture (EA) is effective in treating post-ischemic depression (PID), but little is known about how it works at the cellular level. Astrocytes are exquisitely sensitive to their extracellular environment, and under stressful conditions, they may experience aberrant structural remodeling , which that can potentially cause neuroplastic disturbances and contribute to subsequent changes in mood or behavior.Objectives: This study aimed to investigate the effect of electroacupuncture (EA ) on behavioral deficits associated with post-ischemic depression (PID) in mice, and to verify the hypothesis that astrocytic morphology may be involved in this impact.: Wwe established a PID animal model induced by transient bilateral common carotid artery occlusion (BCCAO, 20 min) and chronic restraint stress (CRS, 21 days).EA treatment (GV20+ST36) was performed for three weeks, through from Monday to Friday each week. Depressive -and Anxiety anxiety -like behaviors and sociability were evaluated by using SPT, FST, EPM and SIT. Immunohistochemistry combined with Sholl and cell morphological analysis were was utilized to assess the process morphology of GFAP+ astrocytes in mood-related regions. The potential relationship between morphological changes in astrocytes and behavioral output was detected by correlation analysis.Results: BThe behavioral assays demonstrated that EA treatment induced an overall reduction in behavioral deficits, as measured by the behavioral Z-score. Sholl and morphological analyses revealed that EA prevented the decline in cell complexity of astrocytes in the prefrontal cortex (PFC) and the CA1 region of hippocampus, where astrocytes displayed evident de-ramification and atrophy of the branches. Eventually, the correlation analysis showed there was a relationship between behavioral emotionality depressive behaviors and morphological changes.Our findings imply that EA preventsed both behavioral deficits and structural abnormalities in astrocytes in the PID model. The strong correlation between the behavioral Z-scores and the observed morphological changes, confirms the notion that the weakening of astrocytic processes may plays a crucial role in depressive symptoms, and astrocyte could be a potential target of EA in the treatment of PID.